Season of the machete - Patterson, James, 1947- (New York, NY : Warner Vision Books, 1995)
Vietnam veteran Peter Macdonald finds himself in big trouble when he accidentally sees the face of Damian Rose, a psychopath who along with his wife Carrie, has embarked on a killing spree in the Caribbean.
Adult
Keywords: Murderers -- Fiction; Psychopaths -- Fiction; Abnormal psychology -- Fiction; Adventure fiction; Homicide -- Fiction; Mystery fiction; Caribbean Area -- Fiction; Caribbean Area -- Fiction; Adventure stories